Corona Virus Disease 2019 in situ arterial and venous thrombosis in critically ill patients: a case series - Castro-Verdes,M; Gkouma,A; Wort,J; Ridge,C; Mirsadraee,S; Padley,S; Sheikh,A; Singh,S (European Heart Journal: Case Reports, 2020)
BackgroundCorona Virus Disease 2019 (COVID-19) pneumonitis associated with severe respiratory failure carries a high mortality. Coagulopathy has emerged as a significant contributor to thrombotic complications.Case summaryWe describe two cases of severe COVID-19 pneumonitis refractory to conventional mechanical ventilation and proning position, transferred to our specialist centre for cardiorespiratory failure. Cross-sectional imaging demonstrated concurrent venous and aortic thrombosis with end-organ ischaemic changes. One patient received thrombolysis with a partial response. This could not be offered to the other patient due to a recent haemorrhagic event. Both patients died of multi-organ failure in the hospital.DiscussionConcurrent aortic and venous thromboses are rare. This finding in COVID-19 cases, who were both critically ill patients, likely reflects the strongly thrombogenic nature of this illness which ultimately contributed to poor outcomes. The absence of deep vein thrombosis or a potential systemic source of embolism suggests in situ thrombosis. Further, the management of anticoagulation and thrombolysis is challenging in patients where an attendant bleeding risk exists.